Equity, trust, and commerce - Davies, Paul S. (Law teacher); Penner, J. E. (James E.) (Oxford [UK] ; Portland, Oregon : Hart Publishing, 2017)
"This collection of essays, written by leading commentators from across the common law world, examines a range of topics concerning Equity and Trusts in the commercial context. The essays investigate the way in which doctrines derived from the equitable jurisdiction interact with and shape various areas of the law, including company law, commercial law and agency law. Subjects considered include the difficulties in identifying trust assets in the commercial context; the court's role in supervising the trust; and the remedies available in cases of fiduciary or trustee wrongdoing. This book will be of interest to both academics and practitioners working in these difficult areas of equity and commercial law."--Bloomsbury Publishing.
Equity, shareholders and company law -- Tan Cheng-Han and Wee Meng-Seng -- Some aspects of the intersection of the law of agency with the law of trusts -- Peter Watts -- Equity in the market place : reviewing the use of unconscionability to restrain calls on performance bonds -- Tang Hang Wu -- Certainty, identification, and intention in personal property law -- Michael Bridge -- Floating trusts -- Robert stevens -- Sort of backwards tracing -- James Penner -- Invoking the administrative jurisdiction : the enforcement of modern trust structures -- Richard Nolan -- Trusts, objectivity, and rectification -- Simon Douglas -- The arbitrability of trust instruments : why not? -- Elaine Chew -- Bribery -- Paul S. Davies -- Accessory disloyalty : comparative perspectives on substantial assistance to fiduciary breach -- Deborah A. Demott -- Equitable liability of corporate accessories -- Jamie Glister -- The nature of knowing receipt -- William Swadling -- Exposing third-party liability in equity : lessons from the limitation rules -- Sarah Worthington.
Includes bibliographical references and index.
Also issued in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Electronic reproduction.
Keywords: Commercial law; Equity; Trusts and trustees